Comparison of the Cross-Linking Patterns of Lamprey Fibrinogen and Fibrin by the Action of the Intrinsic Lamprey Factor XIII and Human Factor XIII during the Process of Blood Coagulation - Murtaugh, Patricia A. (Thrombosis and Haemostasis, 1977)
Intrinsic lamprey factor XIII cross-links the γ-chain of lamprey fibrin (50,000 daltons) to the γ-dimer (100,000 daltons). The a-chain (110,000 daltons) is cross-linked very slowly to a-dimer (210,000 daltons) and a-trimer (330,000 daltons). In contrast, human factor XIII, when added in combination with intrinsic lamprey factor XIII, cross-finks the a-chain of lamprey fibrin to a high molecular weight polymer, and any remaining γ-chain is also cross-linked to a polymer. However, the γ-chain that has previously cross-linked to the γ-dimer by the intrinsic lamprey factor XIII remains as a γ-dimer. Factor XIII-free lamprey fibrin cross-links all its subunits (α, β, γ) to high molecular weight polymers when human factor XIII is added. In contrast to human and bovine fibrin where α-chain cross-linking in the process of blood coagulation commences when all of the γ-chain has cross-linked, the lamprey α-chain will begin to cross-link when approximately half of the γ-chain has cross-linked to the γ-dimer.